Implementation of Contextual Learning Model to Improve Cognitive Learning Ability of Grade X Students in Fiqh Subject at MA Hasyimiyah Bancar - Hibrul Umam; Misbahul Munir; Iffatul Kamaliyah; Ning Setia (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
The development strategy and method in learning fiqh subjects in Madrasah Aliyah (MA) with a contextual learning model aims to improve students' cognitive learning abilities in order to create an active learning atmosphere and increase students' enthusiasm and interest. The purpose of the study is to analyze the planning, management, and evaluation of fiqh subject learning from PAI teachers at MA Hasyimiyah Sukolilo Bancar. And this study uses a descriptive method and a qualitative approach, which is through observation with fiqh teachers, using a contextual learning model taught in class X. In managing learning, the contextual learning model is applied through the stages of constructivity, findings, questions, learning communities, modeling, reflection, and also authentic assessment. The discussion of this study is the application of contextual learning in fiqh subjects at MA Hasyimiyah Bancar. The method used is qualitative research and a phenomenological approach, which focuses on the implementation to be carried out, the evaluation model used, and the learning outcomes achieved in contextual model learning in fiqh subjects. And the results show that the learning planning has been done well, including the formulation of objectives, materials delivered, strategies used, correct methods, techniques, and tactics, as well as development in the syllabus, and is ready for comprehensive teaching. The learning outcomes show that students are able to understand in detail the Islamic laws related to muamalah which are carried out in a good and correct manner. In addition, they gain meaningful knowledge in fiqh learning, instill Islamic legal values such as spiritual awareness and skills, and are able to distinguish between halal and haram (riba) buying and selling. This learning also contributes to building strong learning motivation, forming students' characters who are responsible, disciplined, tolerant, and growing honest, polite, and confident attitudes.